PENGEMBANGAN PERANGKAT PEMBELAJARAN KAWASAN EKOWISATA KAMPUNG BATU MALAKASARI SEBAGAI SUMBER BELAJAR GEOGRAFI - Supriatna, Upi (Jurnal Pendidikan Geografi Gea, 2014)
In the process of studying Geography, environment is important as a learning source to avoid the verbalism in learning process. To develop environment as a learning source we need learning device support. Based on that, the purpose of this study was to develop learning device with environment as a learning source. This research pick ecotourism area at Kampung Batu Malakasari as geographic learning source and to develop the learning device in that area. The learning device which developed in this study produced a practical worksheets which equipped with guidelines for teachers, and location overview. These worksheets and its support measured the validity based on didactical, constructional and technical specification. To measure the validity of learning device researcher used delphy method by asking four experts judgement. The worksheets of learning device of the research in Kampung Batu Malakasari had scored 4.56 (excellent), teacher’s guideline scored 4.60 (excellent), and location overview scored 4.54 (excellent). Thus the learning device for the activity in Kampung Batu Malakasari is adequate to be implemented in Geography learning in that location.Keywords: environment, a learning of source, develop a learning device